Supervivencia por estadio clínico de pacientes con cáncer invasivo de tiroides diagnosticado en el Instituto del Cáncer SOLCA Loja durante el período enero 2008 a junio 2009 - Ayala Ayuso, Juan Diego (2018)
Abstract: Objectives: The aim of this research project was to determine the clinical stage overall survival in patients diagnosed with invasive thyroid cancer during the period January 2008 -June 2009, at the Cancer Institute SOLCA Loja. Methods: The study was a descriptive, cross-sectional and retrospective study. The sample consisted of patients diagnosed with invasive thyroid cancer in the January 2008 - June 2009. Data were obtained from medical records. The probability of survival was determined using the Kaplan-Meier method and log-rank test was used to compare the survival distribution between groups. Results: A total of 60 patients diagnosed with invasive cancer were identified. Of the total patients had to exclude 36 patients for not accomplish the inclusion criteria. The final sample of 24 patients, 6 (24%) were clinical stage (CS) I, 5 (20%) EC II, 9 (36%) III EC and 4 (16%) EC IV.